Efikasi Diri dan Kepuasan dalam Pengasuhan Anak : Studi Meta Analisis - Muchlisah, Muchlisah (Universitas Negeri Makassar, 2019)
Parenting satisfaction is an indicator to see the quality of the relationship between parents and children. Satisfaction of parenting is considered important because it has an impact on the formation of psychological dynamics of good parenting. The foundation of many parenting satisfaction is based on the feeling of parents to be competent in caring for their children. Confidence in the ability to care turns out to have a strong relationship with the formation of parenting satisfaction. The correlation between parenting satisfaction and self-efficacy is implicitly discussed in various studies, but only a few directly link the two variables. The meta-analysis study aims to ensure the relationship of care satisfaction with self-efficacy through measuring sampling errors in 21 studies from 15 selected articles. The result is a sufficient correlation (Å™= 0.41) between parenting satisfaction and self-efficacy. It becomes the basis for determining relationship between parenting satisfaction and self-efficacy.Â Keywords: parenting satisfaction, parenting self efficacy, meta-analysis.